Do Smart Parents Raise Smart Children? The Intergenerational Transmission of Cognitive Abilities - Silke Anger; Guido Heineck (Journal of Population Economics, 2010)
Complementing prior research on income and educational mobility, we examine the intergenerational transmission of cognitive abilities. We find that individuals' cognitive skills are positively related to their parents' abilities, despite controlling for educational attainment and family background. Differentiating between mothers' and fathers' IQ transmission, we find different effects on the cognition of sons and daughters. Cognitive skills that are based on past learning are more strongly transmitted between generations than skills that are related to innate abilities. Our findings are not compatible with a pure genetic model but rather point to the importance of parental investments for children's cognitive outcomes.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s00148-009-0298-8
Keywords: J10; J24; I20; 330; Cognitive abilities; Intergenerational IQ transmission; Skill~formation; Bildungsverhalten; Panel; Deutschland